The impact of the real effective exchange rate on South Africa's trade balance - Matlasedi, Nchokoe Tony (My University, 2016)
The purpose of this paper is to ascertain the impact of the real effective exchange rate on South Africa‟s trade balance and whether the J-curve phenomenon and the Marshal-Lerner condition are satisfied in the economy. Using data spanning the period 1980Q1 – 2014Q4, the Autoregressive Distributed Lag (ARDL) bounds test as well as the Johansen cointegration test were employed to test for the long run cointegrating relationship between the variables. The ARDL approach was employed to estimate both the long run and short run models as well as to ascertain whether the Marshal – Learner condition as well as the J-curve phenomenon are satisfied in the RSA economy. The results from the cointegration tests show that there is a stable long run equilibrium relationship between the trade balance, real effective exchange rate, domestic GDP, money supply, terms of trade and foreign reserves. The results from the Autoregressive Distributed Lag long run model show that a depreciation of the ZAR improves the trade balance, thus confirming the MarshalLerner condition. The results further reveal that domestic GDP and money supply both have a significant negative impact on the trade balance in the long run with the terms of trade reported positive as well. Foreign reserves were not found to significantly affect the trade balance in the long run. In the short run, the ARDL error correction model shows that a ZAR depreciation leads to a deterioration of the trade balance, thus confirming the J-curve effect for the RSA economy. The terms of trade effect was reported positive in the short run, thus confirming the Harberger-LaursenMetzler effect (HLME) in the process. Money supply, domestic GDP and foreign reserves are also found to have a significant negative impact on the trade balance in the short run. Finally, the error correction model reveals that about 26% of the disequilibrium in the trade balance model is corrected in each quarter.
Thesis (M. Commerce (Economics)) -- University of Limpopo, 2016
Keywords: Trade balance; Real Effective Exchange Rate (REER); J-Curve effect; Marshall – Learner condition; Autoregressive Distributed Lag (ARDL); Foreign exchange rates -- South Africa; Exchange rate pass-through; Balance of trade -- South Africa